Literatur Review : Sintesis Hidroksiapatit Dari Limbah Tulang Sapi Menggunakan Metode Hidrotermal - Etih Hartati; Khoirunisa Ameilia Rahmawati; Djaenudin; Herlian Eriska Putra (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
Indonesia is one of the countries with high beef consumption and production, resulting in large amounts of bone waste, especially rib bones, every year. This bone waste is generally not optimally utilized and has the potential to cause environmental problems. In fact, cow bones, including ribs, contain a high-value mineral compound called hydroxyapatite (Ca₁₀(PO₄)₆(OH)₂). Hydroxyapatite is an inorganic compound with a crystal structure and composition similar to human bone and tooth tissue, making it a highly potential material in the biomedical field, especially as a raw material for dentures, bone implants, and bone fillers. Through environmentally friendly technological approaches such as the hydrothermal method, bone waste can be processed to extract pure hydroxyapatite. This process involves heat and pressure treatment in a closed device that can remove organic components without damaging the mineral structure. The synthesized hydroxyapatite has a composition and crystal structure similar to human hard tissue, making it highly potential for use as a base material in medical applications, especially for dental prostheses.